INSTRUMEN TES THREE TIER MULTIPLE CHOICE SEBAGAI DETEKSI MISKONSEPSI PADA MATERI ASAM BASA - Rizka S Putri; pandu jati laksono (Chemistry Education Study Program Sriwijaya University, 2022)
Misconception is defined as a result of someone's mistake in understanding a concept. This research was conducted with the aim of proving students' misconceptions on acid-base material using a three-tier multiple choice test instrument, and determine the factors that influence the occurrence of misconceptions in students. The type of research.used is qualitative research with a descriptive approach. The research was carried out in high schools in Palembang for the academic year 2021/2022 with 35 people. Data collection used a misconception test instrument, teacher and student interviews. The results showed misconceptions on acid-base material with an overall average of 54.33%. The results expected that the three-level multiple choice test instrument can be used by teachers to identify misconceptions that occur in other students.